Influence of hypovitaminosis D on the condition of patients before and after joint replacement (literature review) - Povoroznyuk, Vladyslav; Dedukh, Ninel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The joint replacement is one of the most common orthopedic procedures and is an effective method to restore joint function, patient's activity, to correct limb discrepancy and to eliminate pain syndrome. Over the past few decades, the success of joint replacement has led to a sharp increase in the number of surgeries performed annually all over the world, including Ukraine. However, despite of a significant number of long-term positive outcomes of this surgical intervention, minimization of postoperative complications remains a topical issue for surgeons. The unmodifiable and modifiable risk factors are distinguished, among them a special attention is paid to the vitamin D, which has a pleiotropic effect on the organs and tissues. A literature review highlights the prevalence of vitamin D deficiency and its insufficiency in patients before and after the hip or knee arthroplasties. Some negative effects of this surgical treatment were detected at hypovitaminosis, and being proven by clinical studies: increased rates of periprosthetic joint infection and revision surgeries, length of patients’ hospitalization. The reference data on the normal vitamin D concentration in blood serum reveal its antibacterial effect, which helps to reduce the risk of periprosthetic infection; to increase muscle strength and to reduce the tendency of falls. Further research is needed to determine the relationship between the vitamin D levels and state of patients after joint arthroplasty. The study of the vitamin D therapy and its effect on the condition of patients before and after arthroplasty would be especially promising.